2022
DOI: 10.1002/nau.24884
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of urinary tract infection: A systematic review and meta‐ethnography

Abstract: Aim To understand the experience of urinary tract infection (UTI) by synthesizing primary qualitative research findings and developing a conceptual model that illustrates this experience. Method A systematic search of Medline, PsychInfo, Embase, and CINAHL from inception to August 2020 to find qualitative research exploring the experience of UTI. Qualitative evidence synthesis in the form of meta‐ethnography was undertaken. Findings are reported in keeping with eMERGe guidance. Results We included 16 qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 41 publications
3
25
0
1
Order By: Relevance
“…( 23) These studies and our data suggest that reducing antibiotic use (e.g., through delayed prescriptions, nonantibiotic strategies, SAWB) appears more acceptable for women with less severe, uncomplicated UTIs; if there was evidence that these approaches are safe; and if the benefits of these approaches were explained. Our data agreed with the findings of the meta-ethnography, (17) including the impact of UTIs on the whole body, quality of life and activities, and a need for information and cure. This highlights the need for effective (including optimal antibiotic and non-antibiotic) treatments to resolve painful UTI symptoms and prevent long-term, life-changing complications.…”
Section: Strengths and Limitationssupporting
confidence: 90%
“…( 23) These studies and our data suggest that reducing antibiotic use (e.g., through delayed prescriptions, nonantibiotic strategies, SAWB) appears more acceptable for women with less severe, uncomplicated UTIs; if there was evidence that these approaches are safe; and if the benefits of these approaches were explained. Our data agreed with the findings of the meta-ethnography, (17) including the impact of UTIs on the whole body, quality of life and activities, and a need for information and cure. This highlights the need for effective (including optimal antibiotic and non-antibiotic) treatments to resolve painful UTI symptoms and prevent long-term, life-changing complications.…”
Section: Strengths and Limitationssupporting
confidence: 90%
“…UTIs are mild bacterial illnesses that are usually treated with ABs, [14] but which can be stigmatizing and reduce quality of life. [15] Globally, over 150 million individuals are diagnosed with UTIs each year, most of whom are women. [16] Empiric use of ABs globally to treat UTIs contributes to ABR of the uropathogens responsible (typically Escherichia coli and other Enterobacteriacae), and presents a growing challenge to effective treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Outside of these studies, less emphasis was placed on symptom severity. Similarly, in terms of psychological distress, although Izett-Kay et al found that UTIs had a negative “impact on quality of life and [an] associated psychological toll”, they did not present the same depth of despair that some of our participants experienced (e.g., depression or suicidal ideation) [ 21 ].…”
Section: Discussionmentioning
confidence: 64%
“…Other themes, such as the pervasive impacts of UTIs on life, psychological tolls, and lack of support, empathy, and awareness of the UTI burden among clinicians, were detected in studies including patients with either recurrent or sporadic UTIs. For example, a recent systematic review that analyzed 16 qualitative studies found overlap among the following themes: the disruptive nature of UTIs on patients’ lives, their negative impact on quality of life and associated psychological toll, and a lack of acknowledgment and empathy from some clinicians, summarized as “ being heard, seen and cared for with dignity ” [ 21 ]. A recent study that interviewed 65 women with sporadic or recurrent UTIs from the US ( n = 40) or Germany ( n = 25) also uncovered several limitations that impacted quality of life and strong emotional responses to these limitations and treatment failures, including anxiety, frustration, helplessness, isolation, and embarrassment [ 16 ].…”
Section: Discussionmentioning
confidence: 99%